2022
DOI: 10.3390/su14041957
|View full text |Cite
|
Sign up to set email alerts
|

On the Opportunities of the Soundscape Approach to Revitalise Acoustics Training in Undergraduate Architectural Courses

Abstract: Soundscape research has been gaining prominence in studies on the built environment. The soundscape concept is defined as the acoustic environment as perceived and/or understood by a person in context. Compared with traditional building acoustics, the soundscape concept brings interesting perspectives—but also challenges—for undergraduate architectural curricula, where it tries to strike a balance between qualitative and quantitative methodologies, a theoretical approach that in the context of soundscape studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Embedding soundscape and the ISO 12913 into higher education and professional training can advance the implementation agenda. Engagement by educators (e.g., Milo, 2020;Xiao et al, 2022) and leading industry stakeholders will certainly make the difference in this sense. Quoted from the discussions: "How to quantify the values of soundscapes and holistic well-being from soundscapes will be the key challenge.…”
Section: Building Workability Through Case Studies Training and Impac...mentioning
confidence: 99%
“…Embedding soundscape and the ISO 12913 into higher education and professional training can advance the implementation agenda. Engagement by educators (e.g., Milo, 2020;Xiao et al, 2022) and leading industry stakeholders will certainly make the difference in this sense. Quoted from the discussions: "How to quantify the values of soundscapes and holistic well-being from soundscapes will be the key challenge.…”
Section: Building Workability Through Case Studies Training and Impac...mentioning
confidence: 99%
“…Training providers may also create a course to inform professionals to promote practical smellscape applications. In another human sense, the need for soundscape education in undergraduate curricula has been recently advocated by Xiao J, et al [59]. The authors outline how soundscape can be integrated into teaching building acoustics in undergraduate architectural courses.…”
Section: Education and Trainingmentioning
confidence: 99%
“…The recent literature indicates a tendency towards utilizing experience-based and hands-on approaches. Positive feedback was obtained from methods such as teaching the students how to use measurement devices, how to make sound recordings, and assigning them to create sound maps along with soundwalks [2,4,10,11]. Sharing ongoing acoustical projects and experiences, giving real-life examples, and organizing laboratory visits were found to be effective in capturing the students' interests in the subject [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that these approaches helped students better understand the practical implications of their theoretical information. Examples of the case-based approach include investigating the acoustical qualities of an existing space, taking measurements in the given space, proposing acoustic design solutions, and running acoustical simulations to test those solutions [2,4,11,13]. The design-based approach, on the other hand, comprises designing spaces with the inclusion of acoustical criteria and running simulations to test and improve the designs [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation